Shifting to Centripetalism in Pacific Asia. Issue 3 (3rd July 2022) - Reilly, Benjamin
ABSTRACT: This paper examines the shifting approaches to ethnic representation in the multi-ethnic democracies of Pacific Asia (that is, Southeast Asia and the Southwest Pacific). While Tan and Preece (this volume) chart the range of quotas and seat reservations across Asia, I argue that more integrative approaches to the political representation of ethnicity are also evident in Asia's new and emerging democracies. Comparative institutional analysis shows a shift in ethnic inclusion in Asia towards more aggregative electoral processes, pan-ethnic political parties, and oversized multiethnic executive governments. With few exceptions, the region has abandoned the idea that cleavages of ethnicity, region or language should be replicated directly in the political architecture of the state, seeking instead to aggregate social cleavages into majoritarian multiethnic institutions. This marks a change from earlier decades, and highlights a regional shift towards more 'centripetal' models of institutional design.